Profitabilitas menjadi pemediasi untuk variabel yang mempengaruhi struktur modal (Studi pada Bank Umum Syariah di Indonesia periode 2016-2020) - Indah Lestari (J-EBIS (Jurnal Ekonomi dan Bisnis Islam), 2021)
The purpose of this study is to find out and analyze whether there is an Influence of Liquidity, Growth Opportunity, Asset Structure, and Non Debt Tax Shield on Capital Structure with Profitability as an Intervening Variable in Islamic Commercial Banks Registered at OJK 2016-2020 ". This research is a quantitative research using data sources derived from secondary data, namely the annual report. The sampling technique used in this research is purposive sampling technique. Of the 14 Islamic commercial banks registered with the OJK, only 11 are in accordance with the sample criteria in this study. This study uses the Eviews 9 application as a tool for data processing. The analytical methods used in this research are stationarity test, panel data regression model test, classical assumption test, regression test, and path analysis test. The results obtained in this study are liquidity has a significant negative effect on capital structure. Growth opportunity and asset structure have a significant positive effect on capital structure. Meanwhile, the non-debt tax shield and profitability variables have no significant positive effect on capital structure. Liquidity has no significant negative effect on profitability, growth opportunity has no significant positive effect on profitability. Asset structure has a significant positive effect on profitability, while non-debt tax shield has a significant negative effect on capital structure. From the results of the path analysis conducted in this study, profitability was not able to mediate the variables of liquidity, growth opportunity, and non-debt tax shield on capital structure, but for the asset structure variable profitability was able to mediate the influence of asset structure on capital structure.